Constitutional Protection Of Indonesian Migrant Fishers After The Ratification Of ILO Convention No. 188: Harmonizing National Law And International Labour Standards - Kasmin; Rumadi; Piter Ndetu Shan Dji; Hoirotul Mazruah (CITACONOMIA : Economic and Business Studies, 2026)
This study examines the constitutional and international-law implications of Indonesia's ratification of the International Labour Organization Work in Fishing Convention, 2007 (No. 188), and formulates a harmonization model for the protection of Indonesian migrant fishers. The research uses a normative juridical method with statutory, treaty, case, and conceptual approaches. Primary legal materials include the 1945 Constitution, Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers, Government Regulations Nos. 59 of 2021 and 22 of 2022, Presidential Regulation No. 25 of 2026, Constitutional Court Decision No. 127/PUU-XXI/2023, ILO Convention No. 188, the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, and ASEAN instruments on migrant fishers. The study finds that Indonesia already possesses a constitutional and statutory basis for protection throughout the migration cycle, and the Constitutional Court has confirmed that migrant fishing vessel crews fall within the protective scope of Law No. 18 of 2017. Nevertheless, ratification of Convention No. 188 exposes continuing normative and institutional gaps concerning sector-specific definitions, recruitment fees, vessel-owner responsibility, hours of rest, occupational safety and health, social-security portability, repatriation, inspection, transnational jurisdiction, and access to remedies. The article proposes a four-pillar harmonization model: regulatory consolidation with sector-specific differentiation; rights-based licensing and due diligence; integrated transnational enforcement among sending, receiving, flag, port, and coastal States; and effective remedies supported by social protection and worker participation. These reforms should be completed before Convention No. 188 enters into force for Indonesia on 10 June 2027